Outcome of Single-stage Multi-ligament Reconstruction: A Retrospec- tive Observational Study - Bista, Rohit; Joshi, Amit; Basukala, Bibek; Singh, Nagmani; Sharma, Rajiv; Tripathi, Navin; Pradhan, Ishor (Nepal Orthopaedic Association Journal, 2023)
Introduction:Multi-ligament injuries of the knee can cause significant functional impairment. It is uncommon, and treatment is still controversial. The main controversies are around staged versus single-stage surgery. There is scanty literature on the functional outcome of the single-stage multi-ligament reconstruction. Moreover, less is known about the outcomes following single-stage multi-ligament reconstruction in the context of Nepal. We have been practicing single-stage reconstruction for multi-ligament injuries for the last few years at our center. This study was conducted to evaluate the functional outcome after single-stage multi-ligament reconstruction in our setup. Methods: The records of 75 patients who underwent single-stage multi-ligament reconstruction were retrospectively re- viewed. All the patients were interviewed by telephone and face-to-face using set questionnaires. The KOOS QoL, Lysholm, and IKDC scores were used to evaluate outcomes. The data analysis was done using SPSS 20. Student’s t-test and Chi- squared test were used to calculate the p-value for parametric and nonparametric variables. p-value of less than 0.05 was considered to be significant. Results: The mean age of patients who underwent multi-ligament reconstruction was 36.63 years. Among 75 patients, 51 were males, and 24 were females. 50 (66.7%) had RTA, 20 (26.7%) had fall injuries, 3 (4%) had a sports injury, and 2 (2.7%) had other injuries. The mean KOOS QoL, Lysholm, and IKDC scores were 71.19, 85.85, and 75.92, respectively. Conclusion: This study found that more than 77% of patients undergoing single-stage multi-ligament reconstruction have good to excellent outcomes.